KORELASI ANTARA POLA PEMBINAAN AKHLAK DENGAN PERILAKU PESERTA DIDIK KELAS XI PONDOK PESANTREN DARUL AMAN GOMBARA MAKASSAR - B, Muhammad Rusmin (Universitas Islam Negeri Alauddin Makassar, 2020)
The results of the moral development of the students of class XI of the Darul Aman Gombara Islamic Boarding School in Makassar are quite good. This is based on a questionnaire distributed and interviews with several teachers, not found any students who have committed acts that violate the norms of behavior / morals. Behavior of students of class XI Darul Aman Gombara Makassar Islamic Boarding School which obtained the highest score was 87 and the lowest score was 67. The average value obtained from 30 students was 78.3. So it can be concluded that the behavior of students of class XI Darul Islamic Boarding School safe in Gombara Makassar is included in both categories. The relationship between moral development and the behavior of students in class XI Darul Aman Gombara Islamic Boarding School Makassar, namely the level of relationship is classified as very strong. In the correlation coefficient table and the t test results obtained rtable is 0.99> 0.361, then H0 is rejected and H1 is accepted. This can be concluded that there is a correlation or the relationship between moral development with the behavior of students of class XI Darul Aman Gombara Islamic Boarding School in Makassar, with a very strong correlation level.